Research progress on pyroptosis regulated by mesenchymal stem cell-derived exosomes - Yang, Tingyu; An, Jiapan; Xu, Xinqi; Li, Bin; Dou, Zhimin (Frontiers in Immunology, 2025)
Pyroptosis is a newly discovered form of inflammatory programmed cell death, which is frequently involved in the occurrence and development of various diseases. The primary mechanism underlying pyroptosis is the formation of membrane pores mediated by activated pyroptosis-related proteins. The expression levels of these pyroptosis-related proteins serve as crucial biomarkers for assessing the degree of pyroptosis. Modulating pyroptosis can alleviate tissue and organ damage in diseases and promote tissue and organ repair. Therefore, regulating pyroptosis is considered a potential therapeutic strategy. In recent years, mesenchymal stem cell-derived exosomes (MSC-Exos) have emerged as a novel therapeutic tool for pyroptosis due to their carrier properties. MSC-Exos can mitigate tissue damage in various diseases by regulating pyroptosis, thus emerging as strong candidates for disease treatment. Owing to their multifunctionality, MSC-Exos exert different effects by mediating different pathways in the treatment of various diseases. This review summarizes the mechanisms of pyroptosis and the research progress on MSC-Exos-regulated pyroptosis and outlines the existing challenges for the clinical translation of MSC-Exos. Collectively, MSC-Exos can not only precisely regulate the pyroptosis process but also provide new perspectives and approaches for future disease treatment. Therefore, MSC-Exos possess substantial potential for clinical translation.